Digital competences in professorsand studentsof Universidad Central del Ecuador - Cobos Velasco, Juan Carlos (2020)
The currentrole ofprofessors working at the Universitystrengthen due to the connectivity, since in order to teach the students the professors need to know the different technological tools offered by the Web 2.0 through Information Technology and Communication-ICT, reason for which professorsmust be preparednot only to acquire basic knowledge in technology, but to be competent to apply thisinformationin their teaching practices. The objective of this research is to know the digital skills of future professionals based on their perception. For this, 1,799 out of a totalpopulation of 40,000 students ofUniversidad Central del Ecuadoranswered a questionnaire on knowledge perception, application and assessment of digital competences. According to the results, most of the future professionals have a high level of digital competence (especially in basic digital skills); likewise, certain significant contrasts were obtained with respect to agein the area of basic digital skills.In the case of teachers, it was determined that the use of web 2.0 tools causes difficulty in teaching processes, while students have an attachment in their use. The implementation of technological resources in the teaching-learning processpromotes a significant change in institutions of higher education, which will allow to train professionals capable of facing today's society.